Emotional intelligence and family support in parents' acceptance of children with special needs - Salsabila, Naura Devi; Adrian, Yufi (Utan Kayu Publishing, 2025)
The purpose of this research is to examine the influence of emotional intelligence, family support, and demographic variables on parental acceptance of children with special needs, specifically those diagnosed with deafness and cerebral palsy. The study involved 183 participants selected using a non-probability purposive sampling method. Measurement instruments included the Parents’ Acceptance Scale based on Porter, Johnson, and Medinnus' theory, the Emotional Intelligence Scale following Goleman’s (2006) model, and the Family Support Scale adapted from Canavan, Dolan, and Pinkerton (2006). The findings indicate that emotional intelligence and the type of special needs significantly influence parental acceptance, whereas family support dimensions (emotional, advice, concrete, and esteem support) and the child's age were not significant predictors. The R-Square value of 0.174 (17.4%) suggests that the independent variables explain 17.4% of the variance in parental acceptance, with the remaining 82.6% attributed to other factors. Although the R² value appears modest, it highlights the practical significance of emotional intelligence and special needs type in shaping parental acceptance, underscoring the need for targeted interventions. Data collection was conducted during the COVID-19 pandemic, necessitating an extended research period due to lockdown restrictions and limited access to participants. The study underscores the importance of emotional intelligence-based training programs and disability-specific support mechanisms to enhance parental acceptance and resilience. Future research should explore additional psychological and social determinants, particularly in diverse cultural and economic contexts, to develop more comprehensive intervention strategies.